Evaluation of perinatal outcome in high-risk pregnancy at tertiary care centre - Rani, Anupam; Karya, Urmila; Kumari, Sweta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: A high risk pregnancy is one in which mother, fetus or neonate is at increased risk of morbidity or mortality before or after delivery. Hence a relatively small percentage of high risk obstetric population gives rise to a disproportionately high percentage of perinatal and maternal morbidity and mortality. The perinatal outcome can be changed significantly by early detection and special intensive care to high risk pregnancies. Hence Identification of women at risk for these complicated pregnancies with poor outcome is fundamental to antenatal check-up. Methods: 86 high risk antenatal patients attending the outpatient department and labour room were recruited after informed consent.70 normal pregnancy was taken as control group. Perinatal outcomes were compared between high risk and normal pregnancies. Results: Adverse perinatal outcomes were more in high risk pregnancies as compared to normal pregnancies. Conclusions: This study emphasizes on pregnancy related complication leading to adverse perinatal outcome so evaluating patients for high risk factors, early diagnosis, proper antenatal care, prompt treatment, regular follow up, and timely management thus can improve maternal and perinatal outcome.